Prevalence of hepatitis C in people who inject drugs in the cities of Rawalpindi and Islamabad, Pakistan - Waheed, Yasir; Najmi, Muzammil Hasan; Aziz, Hafsa; Waheed, Hasnain; Imran, Muhammad; Safi, Sher Zaman (Biomedical reports, 2017)
Pakistan has the second highest burden of hepatitis C (HCV) in the world. The major route of HCV transmission is contaminated blood or needle sharing. Seventy percent of people who inject drugs (PWIDs) shared needles at some time in their addiction history. The aim of the present study was to estimate the prevalence of HCV in PWIDs in cities of Pakistan. We enrolled 100 PWIDs from the Rawalpindi and Islamabad cities of Pakistan. Blood samples were taken in collection tubes and were subjected to HCV screening by using three rapid HCV screening kits including one step anti-HCV test, onsite HCV Ab rapid test and advance quality rapid anti-HCV test. All 100 blood samples were also subjected to HCV detection by using Elecsys anti-HCV II performed on the Roche Cobas 601 platform based on the ECLIA principle. Seventy-two percent of PWIDs showed the presence of HCV antibodies using the Roche anti-HCV II ECLIA test. We also compared the performance of different rapid kits in comparison with the anti-HCV II by Roche. The sensitivity of CTK kit was 84.72%, which was almost equal to the sensitivity by the SD Bioline HCV and Advanced Quality Rapid HCV tests, which was 83.33%. All three kits showed 100% specificity and positive predictive values. The results showed that the three market competitors of HCV rapid test showed almost equal results. The prevalence of HCV is very high in PWIDs in the capital twin cities of Pakistan. There is dire need to initiate the administration of a hepatitis test and treatment program for both high-risk and the general HCV-positive population. This is the optimal way to achieve HCV control targets established by the United Nations Sustainable Development Goals and Global Health Sector Strategy by WHO.